Perilaku Tarik Baja Struktural dengan Variasi Laju Crosshead - Murdani, Anggit (Jurnal Rekayasa Mesin, 2010)
The objective this research is to investigate the effect of crosshead speed on the tensile behavior of the structural steel which is presented in stress-strain diagram. The experiments were carried out by performing tensile testing of specimens with various crosshead speeds. The crosshead speed was determined by a dial position of 0.2, 0.5, 1, and 2 on the testing machine.In load-free condition, the dial positions give true speed of the crosshead of 0.042 mm/s, 0.27mm/s, 0.663 mm/s, and 1.354 mm/s respectively. The material used in this research is astructural steel which is comparable to the standard of DIN ST37. The result shows that the various crosshead speeds give a different response of the strain rate during the test. The strain rate, whic is resembled by the crosshead speed, begins to increase at the yield point. Also, theultimate stress of the specimens is affected by the crosshead speed. The ultimate stress of the specimens with dial position of 2 increases approximately 25% from that of with dial position of 0.2.Keywords : tensile behavior, crosshead speed, strain rate